Drebrin attenuates atherosclerosis by limiting smooth muscle cell transdifferentiation. Issue 3 (29th April 2021) - Wu, Jiao-Hui; Zhang, Lisheng; Nepliouev, Igor; Brian, Leigh; Huang, Taiqin; Snow, Kamie P; Schickling, Brandon M; Hauser, Elizabeth R; Miller, Francis J; Freedman, Neil J; Stiber, Jonathan A
Abstract: Aims : The F-actin-binding protein Drebrin inhibits smooth muscle cell (SMC) migration, proliferation, and pro-inflammatory signalling. Therefore, we tested the hypothesis that Drebrin constrains atherosclerosis. Methods and results: SM22-Cre + / Dbn flox/flox / Ldlr − / − (SMC- Dbn − / − / Ldlr − / − ) and control mice (SM22-Cre + / Ldlr − / −, Dbn flox/flox / Ldlr − / −, and Ldlr − / − ) were fed a western diet for 14–20 weeks. Brachiocephalic arteries of SMC- Dbn − / − / Ldlr − / − mice exhibited 1.5- or 1.8-fold greater cross-sectional lesion area than control mice at 14 or 20 weeks, respectively. Aortic atherosclerotic lesion surface area was 1.2-fold greater in SMC- Dbn − / − / Ldlr − / − mice. SMC- Dbn − / − / Ldlr − / − lesions comprised necrotic cores that were two-fold greater in size than those of control mice. Consistent with their bigger necrotic core size, lesions in SMC- Dbn − / − arteries also showed more transdifferentiation of SMCs to macrophage-like cells: 1.5- to 2.5-fold greater, assessed with BODIPY or with CD68, respectively. In vitro data were concordant: Dbn − / − SMCs had 1.7-fold higher levels of KLF4 and transdifferentiated to macrophage-like cells more readily than Dbn flox/flox SMCs upon cholesterol loading, as evidenced by greater up-regulation of CD68 and galectin-3. Adenovirally mediated Drebrin rescue produced equivalent levels of macrophage-like transdifferentiation in Dbn − / − and Dbn flox/flox SMCs. During early atherogenesis, SMC- Dbn − / − / Ldlr − / − aortas demonstrated 1.6-fold higher levels of reactive oxygen species than control mouse aortas. The 1.8-fold higher levels of Nox1 in Dbn − / − SMCs were reduced to WT levels with KLF4 silencing. Inhibition of Nox1 chemically or with siRNA produced equivalent levels of macrophage-like transdifferentiation in Dbn − / − and Dbn flox/flox SMCs. Conclusion : We conclude that SMC Drebrin limits atherosclerosis by constraining SMC Nox1 activity and SMC transdifferentiation to macrophage-like cells. Graphical Abstract: